The premium quality guaranteed of the Hungarian Honey - Oravecz, Titanilla Éva (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
Apiary is a sector in the Hungarian agriculture with an international importance, that needs great competence and manpower. Apiary gives 1 % of the Hungarian agricultures’ gross value of production, 3 % of the stock-raising. Food safety issues, environmental impacts, bee health care, hygiene of bee products are also presented. I analyze the data regarding Hungarian food safety, while a wide range of Hungarian bee products are also presented in that aspect. The Hungarian Bee-keeping Association tested honey sold in various outlets, according to the 21.§., 118/2013 (XII.16.) VM-Decree. I will get a closer look at this species question, which is about the honey safety. I examinated the results of the quality controls and several products’ laboratory parameters and limits are also presented. I examined the HMF (Hydroxymethylfurfural), fructose, glucose and sucrose content, diastase activity and the originality of honey. In case of the food adulteration I looked for foreign enzyme and sugar. According to the Codex Alimentarius Hungaricus (1-3-2001/10): “The honey which is made for human consumption or is sold to consumers, should not be broadened by other food ingredient or any other material than the honey itself. The honey must be devoid of any organic or inorganic matter.”